Compassion at work - Lilius, Jacoba (Henry Stewart Talks, 2013)
Introduction to the CompassionLab, Motivations for the research, The personal and organizational cost of pain, Building understanding of compassion at work, What triggers compassion at work?, The nature of compassionate responding, Why compassion at work matters, Enabling compassion at work, Conclusions: Key insights provided and questions raised by our research